Exploring the Roles of Gender and Ethnicity as Antecedents of Trust in 3D Immersive Electronic Commerce - Kung-Keat, Teoh; Eze Uchenna, Cyril (2008)
The next generation Internet is expected to be a complete visual, audio experience, and possibly haptic experience. It will emulate real life experiences as virtual worlds filled with virtual objects simulating real world interact with users naturally. Users are also expected to be represented in avatars, providing a sense of self-identity and personality. While the Internet is likely to move into 3D format with Second Life leading the pack, the fate of electronic commerce in this light has largely been unexplored. Questions as to the effects and impact of such virtual electronic commerce, especially virtual 3D malls or stores in an immersive online environment on web users are still not answered. This study forms an early exploration on the effects and impact of gender and ethnicity towards the perceived usefulness, perceived ease of use, trust, and intended use of the electronic commerce on the 3D online virtual malls or stores. Its results show that these factors have a significant impact on how such online malls and stores are perceived by users in Malaysia. The implications and proposed future directions of the study are also discussed.